The whole set of the constitutive promoters recognized by four minor sigma subunits of Escherichia coli RNA polymerase. - Tomohiro Shimada; Kan Tanaka; Akira Ishihama (PLoS ONE, 2017)
The promoter selectivity of Escherichia coli RNA polymerase (RNAP) is determined by the sigma subunit. The model prokaryote Escherichia coli K-12 contains seven species of the sigma subunit, each recognizing a specific set of promoters. For identification of the "constitutive promoters" that are recognized by each RNAP holoenzyme alone in the absence of other supporting factors, we have performed the genomic SELEX screening in vitro for their binding sites along the E. coli K-12 W3110 genome using each of the reconstituted RNAP holoenzymes and a collection of genome DNA segments of E. coli K-12. The whole set of constitutive promoters for each RNAP holoenzyme was then estimated based on the location of RNAP-binding sites. The first successful screening of the constitutive promoters was achieved for RpoD (σ70), the principal sigma for transcription of growth-related genes. As an extension, we performed in this study the screening of constitutive promoters for four minor sigma subunits, stationary-phase specific RpoS (σ38), heat-shock specific RpoH (σ32), flagellar-chemotaxis specific RpoF (σ28) and extra-cytoplasmic stress-response RpoE (σ24). The total number of constitutive promoters were: 129~179 for RpoS; 101~142 for RpoH; 34~41 for RpoF; and 77~106 for RpoE. The list of constitutive promoters were compared with that of known promoters identified in vivo under various conditions and using varieties of E. coli strains, altogether allowing the estimation of "inducible promoters" in the presence of additional supporting factors.